Combined flexure and web crippling strength of a low-ductility high strength steel decking: Experiment and a finite element model - Akhand A.M.; Wan Badaruzzaman W.H.; Wright H.D. (2023)
Profiled decking or sheeting of high strength low-ductility steel (ASTM611 Grade E) is a relatively new development in building construction industry. Due to inadequate information, the major international codes of design practices are yet to include this steel, and apply additional restrictions on their design and use. This type of decking shows high sensitivity to distortional as well as local buckling. Strength of such decking under combined flexure and web crippling as well as moment-rotation capacity are of principal concern if such decking is to be designed as a continuous structure to achieve better economy. This paper describes an experimental study of the behaviour of re-entrant decking of low-ductility steel under combined web crippling and flexure. Based on this experimental study, a nonlinear finite element model has been proposed which can predict the moment-rotation characteristics of such decking with reasonable accuracy. 2004 Published by Elsevier Ltd.